382. PREDICTION OF ESOPHAGEAL SQUAMOUS CELL CARCINOMA (ESCC) RISK BY ASSESSING EPIGENETIC AND GENETIC FIELD DEFECTS. (24th September 2022) - Kishino, Takayoshi; Yakashita, Satoshi; Lee, Yi-Chia; Wu, Ming-Shiang; Okano, Keiichi; Ushijima, Toshikazu
Abstract: Field defects are important for human carcinogenesis. Such field defects are formed by accumulation of epigenetic and genetic alterations. Here, we aimed to predict cancer risk of ESCC by assessing epigenetic and genetic field defects. First, we focused on epigenetic field defects. Genome-wide methylation analyses were performed using the esophageal mucosae, and methylation risk markers were isolated. Methylation levels of the isolated candidate genomic regions were measured by quantitative methylation-specific PCR (qMSP). Second, we focused on genetic field defect. However, measurement of such point mutations has been very difficult in human DNA samples, because of their very low frequencies. We established a novel method to the such rare mutations at the 10–6 per bp level in non-cancerous mucosae: the 100-copy method. Both epigenetic and genetic alterations were accumulated in a stepwise manner according to the risk level of the esophageal mucosae. The odds ratio to distinguish patients with ESCC (high-risk group) from healthy individuals exposed to risk factors, namely, alcohol drinking, betel quid chewing, and cigarette smoking (ABC) (intermediate-risk group), were 10.9 (AUC:0.787) by assessment of epigenetic alterations and 18.2 (AUC:0.791) by assessment of genetic alterations. Integration of genetic and epigenetic markers could predict the ESCC risk more precisely [Yamashita, PNAS, 115:1328, 2018].